IDENTIFYING ESSAY WRITING DIFFICULTIES AND INFLUENCING FACTORS AMONG SOPHOMORE STUDENTS - Fatimah, Siti; Amalia, Shynta; Dwi Amrina, Rizqy (Universitas Putera Batam, 2025)
The ability to write essays is fundamental in academia, as it helps students articulate their thoughts, construct arguments, and apply critical thinking skills. Nevertheless, numerous second-semester students encounter challenges in mastering this skill, which can negatively affect their academic development. This research aims to examine the specific obstacles and contributing factors experienced by second-year students enrolled in the English Education Study Program at UIN Raden Fatah Palembang. Drawing on the frameworks proposed by Nenotek et al. (2022) and Alfaki (2015), this research adopts a qualitative approach. Sixteen participants were selected using homogeneous sampling, and data were gathered through interviews and analyzed using thematic analysis. The results show that students faced multiple difficulties in essay writing, particularly in the areas of content, organization, discourse, and mechanics. These difficulties stemmed from various sources, including the complexity of the writing process, low student motivation, inadequate time allocation, infrequent writing practice, and delayed instructor feedback. The findings suggest that such difficulties significantly influence students’ overall academic performance.